2009
DOI: 10.1002/hed.21174
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition impact symptoms: Key determinants of reduced dietary intake, weight loss, and reduced functional capacity of patients with head and neck cancer before treatment

Abstract: Symptoms present before treatment may adversely affect the dietary intake, weight, and functional capacity of patients. Symptom treatment and management is critical to weight loss prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
110
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(122 citation statements)
references
References 47 publications
1
110
1
6
Order By: Relevance
“…Adequate nutrition is an important clinical concern, and weight loss before and during treatment has been found to be strongly associated with pretreatment swallowing dysfunction [23][24][25]. A swallowing difficulty can restrict the range of food textures, compromising oral intake and patient satisfaction [25].…”
Section: Dietmentioning
confidence: 99%
“…Adequate nutrition is an important clinical concern, and weight loss before and during treatment has been found to be strongly associated with pretreatment swallowing dysfunction [23][24][25]. A swallowing difficulty can restrict the range of food textures, compromising oral intake and patient satisfaction [25].…”
Section: Dietmentioning
confidence: 99%
“…Of particular concern is the statistic that in Taiwan, approximately 85% of oral carcinoma patients are habitual users of betel quid, which is strongly associated with adult metabolic syndrome [1,7]. These factors of cancerrelated malnutrition and carcinogen exposure have a significantly negative prognosis [8]. Furthermore, the surgery for stage IV oral cavity cancer patients is much more destructive than for early-stage patients so that postoperative chewing/ swallowing problems and cosmetic damage are inevitable.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, a prospective longitudinal study of patients receiving chemotherapy found higher numbers of S-NIS correlated with a poorer quality of life 2 and in head and neck cancer patients, multiple S-NIS prior to treatment are associated with reduced dietary intake and functional capacity. 12 A low-cost intervention such as nutritional counseling in patients with head and neck cancer improves symptoms (e.g., dysguesia and nausea) as well as overall quality of life. 13 Among other possible contributors to secondary cachexia, low testosterone is very common and associated with fatigue and poor appetite in patients with cancer, 14 whereas hypothyroidism prevalence may be as high as 30% in patients treated with radiotherapy for head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%